Hamsters immunized with formalin-inactivated SARS-CoV-2 develop accelerated lung histopathological lesions and Th2-biased response following infection - Rineke de Jong; Sandra Vreman; Katrin E. Wiese; Nora M. Gerhards; Kevin R. Bewley; Yper Hall; Francisco Javier Salguero; Miles Carroll; Rik L. de Swart; Jose L. Gonzales; Nadia Oreshkova (npj Vaccines)
Abstract One of the concerns regarding vaccine safety during the COVID-19 pandemic was the potential manifestation of vaccine-associated enhancement of disease (VAED) upon SARS-CoV-2 infection. To investigate the suitability of the Syrian hamster model to test for VAED, we immunized animals with an experimental formaldehyde-inactivated, alum-adjuvanted SARS-CoV-2 vaccine preparation. In two independent experiments, challenge infection did not result in an enhancement of the clinical disease in vaccinated animals compared with mock-vaccinated animals. However, at early timepoints (2–5 days) post-challenge, lung histopathology progressed faster and was more prominent in vaccinated hamsters and lung tissue showed elevated mRNA levels of IL-4 and IL-13. At later time points, cytokine responses and lung pathology were comparable between vaccinated and mock-vaccinated hamsters, underscoring the transient nature of the pathological aggravation. With this work we show that the Syrian hamster model can be used to assess possible vaccine safety considerations in a preclinical setting.